LOKAKARYA DAN PELATIHAN TEKNOLOGI MEDIA GEREJA DI MEDIA SEVEN PRODUCTION - Robertus Suryadi; Eko Agus Setiawan; Stefan Rumaijuk (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The church needs to make some efforts to help the church where we belong, especially in terms of evangelizing to all people of this age. That's why this media technology as a means for me to realize this longing. We often find in today's churches, there is still a lot of communication to the congregation that must be done digitally or through technology media, but it is still done conventionally. In addition, especially so many churches are still not